2023
DOI: 10.1056/nejmoa2207586
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Conserving Surgery with or without Irradiation in Early Breast Cancer

Abstract: BackgroundLimited level 1 evidence evaluates the omission of postoperative radiotherapy after breast-conserving surgery in older women with hormone receptor positive early breast cancer receiving adjuvant endocrine therapy. MethodsA phase 3, randomized trial of omitting irradiation was performed in 1326 women aged ≥65 years with pT1-T2 (≤3cm), pN0, hormone receptor positive breast cancer treated by breast-conserving surgery with clear margins and adjuvant endocrine therapy. Patients were randomly assigned to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 37 publications
4
105
0
2
Order By: Relevance
“…Women ≥ 70 years of age comprise 30% of our cohort. While the CALGB 9343 and PRIME II trial (13,14,15) offer the option of no RT for those patients despite the increased -albeit still low risk of local failure, our study shows that IORT could be an alternative option for this group of patients who want the bene t of adjuvant RT without the added inconvenience of daily visits. This is currently being explored in the phase II prospective TARGIT-E trial (16).…”
Section: Discussionmentioning
confidence: 73%
“…Women ≥ 70 years of age comprise 30% of our cohort. While the CALGB 9343 and PRIME II trial (13,14,15) offer the option of no RT for those patients despite the increased -albeit still low risk of local failure, our study shows that IORT could be an alternative option for this group of patients who want the bene t of adjuvant RT without the added inconvenience of daily visits. This is currently being explored in the phase II prospective TARGIT-E trial (16).…”
Section: Discussionmentioning
confidence: 73%
“…In total, 1,326 patients were studied and managed with WBRT or observation. Overall survivals were equal; however, there were very high local recurrence rates in the observation arm, as shown in Figure 2 (9.5% versus 0.9% between observation vs. RT arms, respectively) [58]. This again speaks more in favor of IORT in low-risk patients considering their QOL (e.g., the fear of recurrence as well as the inconvenience of requiring surveillance periodically) and the added costs of surveillance.…”
Section: Recommendations For Patients and Familiesmentioning
confidence: 93%
“…One of the recent options can be even completely omitting RT in EBC in very selected populations [ 58 ]. In a recent study, Kunkler et al reported the results of a phase III randomized study in women 65 years or older with eligibility criteria similar to that of IORT eligibility for EBC.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations